Genotoxic stress accelerates age-associated degenerative changes in intervertebral discs - Nasto, Luigi A. (2012)
Intervertebral disc degeneration (IDD) is the leading cause of debilitating spinal disorders such as chronic lower back pain. Aging is the greatest risk factor for IDD. Previously, we demonstrated IDD in a murine model of a progeroid syndrome caused by reduced expression of a key DNA repair enzyme. This led us to hypothesize that DNA damage promotes IDD. To test our hypothesis, we chronically exposed adult wild-type (Wt) and DNA repair-deficient Ercc1(−/Δ) mice to the cancer therapeutic agent mechlorethamine (MEC) or ionization radiation (IR) to induce DNA damage and measured the impact on disc structure. Proteoglycan, a major structural matrix constituent of the disc, was reduced 3-5x in the discs of MEC- and IR-exposed animals compared to untreated controls. Expression of the protease ADAMTS4 and aggrecan proteolytic fragments were significantly increased. Additionally, new PG synthesis was reduced 2-3x in MEC- and IR-treated discs compared to untreated controls. Both cellular senescence and apoptosis were increased in discs of treated animals. The effects were more severe in the DNA repair-deficient Ercc1(−/Δ) mice than in Wt littermates. Local irradiation of the vertebra in Wt mice elicited a similar reduction in PG. These data demonstrate that genotoxic stress drives degenerative changes associated with IDD.